PENGAPLIKASIAN TEKNIK SMOCKING PADA BUSANA DEMI-COUTURE - Susiana Susiana (Moda : The Fashion Journal, 2022)
In the development of fabric manipulating techniques, there are several types of fabric processing techniques in the community that can be used as decorative elements in decorating fabrics, namely smocking. Smocking is one of the surface techniques that require hand skills in turning a plain cloth into an embossed patterned cloth. Along with the development of smoking techniques, the creative industry can utilize and develop a piece of cloth into creativity that has a high selling value. In addition, smocking can be used as an alternative that can provide beauty in clothing with various varied forms. Based on the process of making smoke, it requires high hand skills, so this surface has the potential to be used as an application for demi-couture clothing. This study aims to develop the potential of the direct smoking technique in demi-couture clothing. The final result of this research is a demi-couture clothing collection by applying the direct smoking technique. This study uses qualitative methods, namely by collecting data such as trend and material observations as well as exploring smoking techniques. Keywords: Demi-couture, Smocking, Surface